Effets et compatibilité de la combinaison champignons endomycorhiziens et fertilisants chez deux graminées de gazon : Poa pratensis L. cv. Park et Agrostis stolonifera L. cv. Penncross. - Podeszfinski, Catherine Maryse. (University of Ottawa (Canada), 1999)
The general objective of this thesis was to study the interactions between AM fungi and turfgrass species in the presence of natural or chemical fertilizers. We had hypothesized that this symbiosis is possible, functional and compatible in the presence of fertilizers. To test this hypothesis, we have set three objectives: (i) estimate colonization rate for three AM fungi: Glomus intraradices, G. mosseae and G. aggregatum on two turfgrass species Poa pratensis L. cv Park and Agrostis stolonifera L. cv Penncross; (ii) evaluate the compatibility between natural and chemical fertilizers and AM fungi, and (iii) compare the effects of AM colonization on different physiological parameters in turfgrass. This study was performed over a period of 17 months between June 1996 and October 1997 on two different sites, Clarence Creek and the Central Experimental Farm (Ottawa), respectively low (46ppm) and high (270ppm) in soil phosphorus status. In total, 96 plots were randomly distributed on each sites. To investigate the dynamic of turfgrass community, we performed a greenhouse experiment following the same experimental design as in the field. (Abstract shortened by UMI.)
Keywords: Biology, Ecology.